The white lady : a novel - Winspear, Jacqueline, 1955- (HarperCollins, 2023)
"A reluctant ex-spy with demons of her own, Elinor finds herself facing down one of the most dangerous organized crime gangs in London, ultimately exposing corruption from Scotland Yard to the highest levels of government"--